Cross-Cultural Adaptation, Validation, and Arabic Translation of the Eustachian Tube Dysfunction Questionnaire (ETDQ-7) - Alkholaiwi, Feras; Alnatheer, Abdullah M.; Theyab, Rami Saud; Alyousef, Meshal; Aldrees, Turki; Dahmash, Abdulmajeed Bin; Alghonaim, Yazeed (International Archives of Otorhinolaryngology, 2022)
Introduction The Eustachian Tube Dysfunction Patient Questionnaire (ETDQ-7) scale is used to assess the effectiveness of the treatment and to determine the severity of the eustachian tube dysfunction (ETD). There is currently no validated Arabic version of the ETDQ-7.Objectives The aim of the present study is to test the validity and the reliability of a translated Arabic version of the ETDQ-7.Methods A multicenter prospective validation study was conducted in Riyadh, Saudi Arabia. The ETDQ-7 was adapted and translated into Arabic using a standard validation methodology. Fifty-one patients diagnosed with Eustachian tube dysfunction and 45 healthy individuals were enrolled in the study. The known-groups method was used in the validity analysis. The test-retest method, item-total score correlation, and internal consistency analysis were used for the reliability analyses.Result The overall internal consistency of the Arabic ETDQ items was measured using Cronbach α (Cronbach α = 0.803). The average and total ETDQ scores were significantly higher in the ETD group (17.6) than in the control group (9.87) (p < 0.001). The results indicate a good to excellent correlation (> 0.7). The area under the curve for the total ETDQ score was 88.6% (95% confidence interval [CI]: 80.3–96.8%)Conclusion The Arabic version of the ETDQ-7 scale is a valid instrument for evaluating ETD. It can also be used as an important tool for diagnosis, patient follow-up, and treatment management.
Keywords: eustachian tube; validation study; translation